Pay Walled Retraction Notices (Bangladesh Journal of Bioethics, 2015)
A retraction of a scientific paper is made, most often due to errors or lack of publishing ethics on the part of authors, or, on occasion, duplicate publication by a publisher in error. The retraction notice that accompanies the retraction is an extremely important document, because it is the only information that provides a background to the public regarding the reason why the manuscript was retracted. In most cases, if the retraction notice is truly transparent, it will contain a few sentences that indicate the reason, and possibly also the authors responsible, among other facts. According to the Committee on Publication Ethics (COPE), retraction notices should be free to view, i.e. open access. This opinion piece exposes how several publishers are selling access to retraction notices, including COPE members, despite, in some cases, being paying COPE members. The business and academic ethics of such an action is thus called into question.Bangladesh Journal of Bioethics 2015 Vol.6 (1):27-39